Assessing phytoplankton community composition in the Atlantic Ocean from in situ and satellite observations - Brotas, Vanda; Ferreira, Afonso; Veloso, Vera; Tracana, Andreia; Guerreiro, Catarina V.; Tarran, Glen Adam; Woodward, E. Malcolm S.; Ribeiro, Lourenço; Netting, Jane; Clewley, Daniel; Groom, Steve B. (Frontiers in Marine Science, 2023)
The Atlantic Meridional Transect (AMT) program (www.amt-uk.org) provides the perfect opportunity to observe the phytoplankton community size structure over a long latitudinal transect 50 o N to 50 o S, thereby covering the most important latitude-related basin-scale environmental gradients of the Atlantic Ocean. This work presents cell abundance data of phytoplankton taxa recently collected during cruises AMT28 and 29 (in 2018 and 2019, respectively) using flow cytometer and microscope observations, as well as the pigment composition of the community, to assess the abundance and spatial distribution of taxonomic groups across the Atlantic. The community size structure showed a clear consistency between cruises at large spatial scale, with a dominance of picoplanktonic Cyanobacteria in oceanic gyres, an increase in all groups in the equatorial upwelling region, and high biomass of microplankton size class at higher latitudes. Phytoplankton carbon biomass for oceanographic provinces, ranged from median values of 10 to 47 mg Carbon m -3 , for the oligotrophic gyres, and South Atlantic (45°S-50 o S), respectively. Satellite images of total chlorophyll a (as a proxy for phytoplankton biomass) as well as the relative contribution of the three phytoplankton size classes were produced for both cruises, and despite the small number of matchups, statistically agreed well with in situ size classes estimated as carbon biomass, constituting the first attempt in the literature to match satellite size classes with in situ data derived from cell abundance. The comparison of community structure between recent cruises (2019, 2018, 2015) and earlier ones (1995)(1996)(1997)(1998) indicates a decrease in the number of diatom-bloom forming species, and an increase in Dinoflagellates, whereas nitrogen-fixing Trichodesmium abundance in tropical Atlantic remains constant. Within the recent period, a relative increase in the median values of picoplankton fraction was seen in SATL region, counterbalanced by a decrease in both nano-and microplankton fractions. Additionally, this study includes a database of species identified by microscopy, which had been interrupted for 20 years, providing a basis for long-term series of phytoplankton species.